Insights into Candida world: the extracellular milieu - Martins, Margarida Isabel Barros Coelho (2010)
Over the last years Candida species, including Candida albicans, Candida dubliniensis, Candida glabrata, Candida krusei, Candida parapsilosis, and Candida tropicalis, have emerged as significant pathogens. This work aimed at bringing insights into Candida species world by the analyses of compounds released into the extracellular medium namely extracellular DNA (eDNA) and alcohol compounds. Concerning eDNA, our results present evidence that this is a key element of the C. albicans biofilm extracellular matrix, contributing to biofilm integrity and antifungal resistance. With respect to extracellular alcohols, the results presented herein show that Candida species secrete a cohort of alcohols that are able to regulate their virulence traits (in vitro and in vivo). Taken together, these studies represent an important contribution to our understanding of the composition of the extracellular milieu of Candida species and its relationship with the regulation of Candida biology, opening the possibility of the development of new treatment and/ or diagnostic strategies to combat candidiasis.